The Business and Management of Ocean Cruises - Vogel, Michael (CABI, 2014)
Cruise lines combine socio-economic, technological and environmental systems in unique ways to form their products. Many managerial functions in the cruise sector deal with tensions, conflicts and uncertainties arising from the interaction of at least two of these systems. The organization of cruise ship management in a hotel department, a technical department and a nautical department, for example, mirrors those three systems, and it is the captain's role to manage the interfaces between the three departments, i.e. between the three systems. Itinerary planning and management needs to strike a balance between the cruise line's economic interest and the passengers' leisure and safety interests, taking fur- ther into account the geographical, climatic, nautical and legal conditions, as well as the ship's technical properties. The cruise itinerary, in turn, determines how tour operations and shore excursions, passenger logistics and ship logistics must be managed. Running a business under such conditions poses particular management challenges. With this book, we aim to capture and document some of the most important and interest- ing managerial challenges associated with ocean cruises. We believe that there is a need for this book because after decades of double-digit growth, the worldwide cruise sector, includ- ing its suppliers and distribution partners, has become a significant employer of people with a wide range of skills and qualifications.